Looking at the law and policy of recycling in Malaysia / Ad'lean Mohd Yusof, Heleyaniiza Mohd Said and Ruzanna Ahmad. - Mohd Yusof, Ad'lean; Mohd Said, Heleyaniiza; Ahmad, Ruzanna (Faculty of Law, 2006)
In Malaysia, the Environment Act is silence on matters relating recycling which deemed to be important. From this research, one of the problems that arising due to recycling is that the level of awareness is too poor among the citizens, the facilities are not sufficient and adequate in order to encourage people to recycle and mostly, there was no law that governed recycling in Malaysia. As compared to foreign law such as laws that governs haulers, law which had been divided between recycling materials, recycling provisions on the matters of penalties and others that had been passed by their legislation. This shows that they take recycling as a serious matter. Moreover, they provide sufficient facilities and encourage their citizens to recycle. Further, if the law is not complied with, penalties will be imposed against them. The level of awareness among their citizens is tremendous where their citizens are more responsible and understand their duties and role to oblige the law. Thus this research will look at the general problems on recycling, comparison between Malaysian law and foreign law such as United States and Japan and recommendations to the loop holes in Malaysian policy.